2020
DOI: 10.20452/pamw.15399
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of combined endobronchial and endoscopic ultrasound-guided needle aspiration in the diagnosis of sarcoidosis: a prospective, multicenter trial

Abstract: organs confirmed by a cyto-or histopathological examination. 2,3,4 Because granulomatous inflammation can be observed in many other diseases with similar clinical and / or radiological features (ie, tuberculosis, mycobacterial or fungal infections, pneumoconiosis, hypersensitivity pneumonia, lymphoma, lung cancer, berylliosis, and also sarcoid reaction, which may accompany or precede IntroductIon Sarcoidosis is a chronic inflammatory disease of unknown etiology. Noncaseating granulomas in various organs, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Similarly, the station of the mediastinal lymph node sampled also has a bearing on the diagnostic yield. A recent study found a positive association between sampling of subcarinal lymph nodes and yield of endosonographic biopsy [19]. This is probably due to ease of sampling this station of lymph nodes.…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, the station of the mediastinal lymph node sampled also has a bearing on the diagnostic yield. A recent study found a positive association between sampling of subcarinal lymph nodes and yield of endosonographic biopsy [19]. This is probably due to ease of sampling this station of lymph nodes.…”
Section: Discussionmentioning
confidence: 95%